How do Libraries Find their Way onto the Semantic Web? - Borst, Timo; Fingerle, Birgit; Neubert, Joachim; Seiler, Anette (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
The First Semantic Web/Linked Data Conference of German libraries took place in Cologne on 24 and 25 November 2009 and revealed much interest in advancing from a web of documents to a web of data. The contributions covered advanced applications at the Library of Congress and the Swedish National library as well as advocacy for linked data approaches and the use of semantic web tools in the library and cultural heritage domain. The German National Library announced the publication of their authority files as linked open data, with first prototypes to become available in mid-2010, and this constituted a highlight of the conference. Discussions about ontologies to be used, application examples and a summary of practical experiences completed the event.